2011
DOI: 10.1093/intqhc/mzr045
|View full text |Cite
|
Sign up to set email alerts
|

Wristbands as aids to reduce misidentification: an ethnographically guided task analysis

Abstract: Wristbands for patient identification are not being used to their full potential. Attention to detail in application and use, especially during handover and transfer, and an appreciation of the role played by 'non-clinical' staff, may offer further gains in patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 22 publications
0
23
0
12
Order By: Relevance
“…Guaranteeing unequivocal patient identification is the main point to prevent mistakes or nonconformities in health care, but it is still challenging and requires well-defined protocols and commitment from professionals (9)(10) . Each healthcare organization has its own identification procedure to keep the process accurate based on standard operating procedures or strategies to improve patient safety (9,(11)(12)(13) . Nevertheless, the identification protocols for wristbands advocate some fundamental measures, such as content clarity, commitment of professionals, registry of the time of placement, removal and substitution of wristbands, description of activities and identification mechanisms in situations in which standard operating procedures cannot be followed, which encompass Evaluation of the risk of misidentification of women in a public maternity hospital Tase TH, Quadrado ERS, Tronchin DMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guaranteeing unequivocal patient identification is the main point to prevent mistakes or nonconformities in health care, but it is still challenging and requires well-defined protocols and commitment from professionals (9)(10) . Each healthcare organization has its own identification procedure to keep the process accurate based on standard operating procedures or strategies to improve patient safety (9,(11)(12)(13) . Nevertheless, the identification protocols for wristbands advocate some fundamental measures, such as content clarity, commitment of professionals, registry of the time of placement, removal and substitution of wristbands, description of activities and identification mechanisms in situations in which standard operating procedures cannot be followed, which encompass Evaluation of the risk of misidentification of women in a public maternity hospital Tase TH, Quadrado ERS, Tronchin DMR.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the most effective approach to help patients to change behaviors and improve results in health care is considered a significant progress in the quality of services (12,26) . Other situations that expose healthcare professionals to the risk of misidentification include high number of patients, incomplete pronunciation and spelling and sound similarity, among others (2,8,19,21,27) .…”
Section: Discussionmentioning
confidence: 99%
“…As rotinas já estabelecidas asseguram uma zona de conforto aos profissionais, enquanto a proposta de reconfiguração das ações pode desencadear sentimento de insegurança, rejeição e medo. Neste aspecto, a difícil tarefa de implantar novas rotinas foi descrita em estudo anterior, reconhecendo que políticas que visam alterar o comportamento dos praticantes na melhoraria da segurança do paciente têm menos possibilidade de sucesso se não levarem em conta as práticas já existentes (15) .…”
Section: Discussionunclassified
“…In a study of how and whether nurses identify patients in a psychiatric hospital setting, it was found that the use of wristbands was erratic and influenced by a psychiatric nursing culture rooted in the belief that (good) nurses know who the patients are 22. The inconsistency in using the patient’s wristband for identification has also been addressed in somatic settings, and it has been shown in simulation tests that as many as 61% of nurses do not discover an unexpected identity error 23,24. This raises a question about how and when nursing culture plays a role in patient safety and whether this brings advantages or barriers.…”
Section: Discussionmentioning
confidence: 99%